PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MODEL KOOPERATIF TIPE PAIRED STORYTELLING PADA SISWA KELAS V SDN 14 KOTO LALANG KOTA PADANG - Khairunnisa; Adrias; Muhammadi; Suriani, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in speaking skills in grade V of SDN 14 Koto Lalang, Padang City. This study aims to describe the improvement of speaking skills in Indonesian language learning using the Paired Storytelling cooperative learning model. The type of research used is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the research were 28 grade V students of SDN 14 Koto Lalang, Padang City. Data collection techniques were carried out through observation, tests, and documentation. The results of the study showed an increase in each cycle. In terms of learning planning, there was an increase from the good category to very good. The implementation of learning also experienced an increase until it reached the very good category. Meanwhile, the results of students' speaking skills experienced an increase from an average score of 74.1 in the first meeting of cycle I to 80.2 in the second meeting, and increased again to 85.2 in cycle II with a level of completeness that has met the success indicators. Based on these results, it can be concluded that the application of the Paired Storytelling type of cooperative learning model can improve the speaking skills of students in class V of SDN 14 Koto Lalang, Padang City.